PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN LEPAS DARI SEGALA TUNTUTAN HUKUM PERKARA PENIPUAN DALAM PUTUSAN NOMOR 362/PID.SUS/2023/PN.CBI - Kinanta, Valentina Riska; Kurniawan, Itok Dwi (Verstek, 2026)
This study aims to determine and describe the considerations of the Cibinong District Court judge in issuing a verdict of acquittal from all charges in a fraud case with the provisions of Article 191 paragraph (2) of the Criminal Procedure Code. This research is a normative or doctrinal legal research with a case approach. The nature used in this study is prescriptive and applied. The sources of legal materials used are primary legal materials and secondary legal materials. The legal material collection technique used is literature study. This study uses a legal material analysis technique with a syllogism method with a deductive mindset. Based on this study, the results obtained are that the Judge's Consideration in issuing a verdict of acquittal from all charges in the fraud case trial in Verdict Number 362/Pid.Sus/2023/PN.Cbi has fulfilled Article 191 paragraph (2) of the Criminal Procedure Code.